Quenching and partitioning steel produced through hot rolling, direct quenching and annealing. Issue 15 (12th October 2016) - Guo, H.; Zhao, A.; Ding, R.; Zhi, C.; He, J.
Abstract : A novel type of quenching and partitioning steel was developed using direct quenching after hot finishing rolling, followed by intercritical annealing, quenching and partitioning (DQ–Q&P) process. The desirable combination of strength and ductility was obtained. The effect of various intercritical annealing temperatures on the microstructures and mechanical proprieties was studied. With the decreasing intercritical annealing temperature, the amount of acicular retained austenite increased, which exhibited a good work-hardening behaviour resulting in enhanced tensile strength and total elongation. After annealing at 740°C, superior mechanical properties, which were the ultimate tensile strength of 1015 MPa and total elongation of 32.22%, were achieved.